Historical female management theorists : Frances Perkins, Hallie Flanagan, Madeleine Parent, Viola Desmond - Williams, Kristin S. (Critical management studies (Series), 2022)
Persuasively arguing for the inclusion of overlooked female figures whilst simultaneously bridging feminist theory and critical historiography, Historical Female Management Theorists features four literary non-fiction, fictitious conversations with historic female proto-management theorists from Canada and the United States: Frances Perkins (1880-1965), Hallie Flanagan (1890-1969), Madeleine Parent (1918-2012), and Viola Desmond (1914-1965). These women have been noted for their contributions in various fields, however their accomplishments and lessons have largely been overlooked by management and organizational history. A variety of archival, biographical and media sources are combined with Williams's own sense-making and learnings to stitch together a believable, but fictional encounter, introducing a method for feminist historical inquiry - ficto-feminism. A blend of auto-ethnography, collective biography and fictocriticism, this new method explores mechanisms to enact personal agency in subject and writer, featuring a novel narrative, storytelling style inspired by fictional writing. Historical Female Management Theorists is essential reading for both feminist scholars and management historians.